Moisture content investigation in the soil samples using microwave dielectric constant measurement method - Shashi K. Dargar; Viranjay M. Srivastava (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The microwaves of typical frequency ranges of 3 GHz to 30 GHz have been in use for remote sensing applications which are progressing rapidly. The microwaves can sense existing moisture in any material that absorbs moisture such as soil or vegetation. In case of soils which may be comprised of variable mix proportionate of solids, liquids or gases and distinct textures subjected to the associated size and the arrangements of soil particles. Hence, the moisture absorption by a specific type of soil used to be different. The inherent physical and electrical properties such as color, texture, grains, dielectric constant, conductivity or permeability, etc. differentiate various soils. In this work, authors present soil moisture measurement by simple estimation of emissivity i.e. the ratio of energy radiated by an object to absorbing the body of same physical temperature. A strategic method of measuring dielectric constant using a microwave signal is used in this research work. The measurement of the dielectric constant of the soils collected from the specific regions and analysis of results has been reported. The proposed method is less complex and can further be used for the identification of soil moisture and agricultural applications.